The Effect of Net Profit Margin on Current Ratio in PT. Siantar Top, PT. Kimia Farma and PT. Gudang Garam Companies Period 2020-2022 - Paskah Pardede; Herlin Munthe (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Net Profit Margin and Current Ratio are two financial ratios used to analyze the financial health of a company. Net Profit Margin is one of the important indicators to assess the financial performance of a company as it provides an insight into how effectively the company generates profits from its operations after considering all costs and expenses. It measures the company’s efficiency in generating profit from each unit of revenue. Companies with a high Net Profit Margin are often considered more attractive to investors because the high net profit indicates the company’s ability to generate strong cash flow and provide good returns to shareholders. Current Ratio is a liquidity ratio that measures a company’s ability to meet its shortterm obligations with liquid assets that can be quickly converted into cash. A high Current Ratio indicates that the company has sufficient current assets to meet its shortterm liabilities. This can provide assurance to investors that the company will not face financial difficulties in paying its obligations when they become due. This research aims to determine the influence of Net Profit Margin on Current Ratio in PT.Siantar Top, PT.Kimia Farma and PT. Gudang Garamwhich were studied on a quarterly basis during the period 2020-2022. This is quantitative research using secondary data, which are the financial statements of each company accessed through the official website of the Indonesia Stock Exchange (BEI). Data analysis was conducted using simple linear regression analysis with the assistance of SPSS softwareversion 25. The result of the research shows that simultaneously or collectively, Net Profit Margin has an influence on Current Ratio and partially, it is found that Net Profit Margin has a significant positive effect on Current Ratio. The coefficient of determination indicates a result of 0,304, which means that rthe influence of Net Profit Margin on Current Ratio is 30,4% while the remaining percentage is influenced by other factors that were not examined in this study.